1995
DOI: 10.1007/bf01447046
|View full text |Cite
|
Sign up to set email alerts
|

Child and adolescent psychotherapy outcomes in experiments versus clinics: Why the disparity?

Abstract: In a recent article, Weisz, Weiss, and Donenberg (1992) compared the effects of child and adolescent psychotherapy in experimental studies and in studies of clinic practice. Here we update that report with new information and we explore 10 possible reasons why, to date, therapy in experiments appears to have shown larger effect sizes than therapy in clinics. We find that beneficial therapy effects are associated with three factors which are more common in research therapy than in clinic therapy: (a) the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
76
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(79 citation statements)
references
References 57 publications
1
76
1
1
Order By: Relevance
“…Positive intervention effects demonstrated by research-based treatments often are not replicated when transported into real-world settings (Weisz, Donenberg, Han, & Weiss, 1995). Although there are no current studies comparing research-based to school-based interventions, a meta-analysis (Weisz, Donenberg, Han, & Kauneckis, 1995) examining treatment implemented in laboratories versus community clinics found that research protocol effect sizes ranged from .71 to .84, compared to effect sizes of −.40 to .29 in clinic settings.…”
mentioning
confidence: 93%
“…Positive intervention effects demonstrated by research-based treatments often are not replicated when transported into real-world settings (Weisz, Donenberg, Han, & Weiss, 1995). Although there are no current studies comparing research-based to school-based interventions, a meta-analysis (Weisz, Donenberg, Han, & Kauneckis, 1995) examining treatment implemented in laboratories versus community clinics found that research protocol effect sizes ranged from .71 to .84, compared to effect sizes of −.40 to .29 in clinic settings.…”
mentioning
confidence: 93%
“…For example, psychosocial treatments validated in randomized trials are more clearly specified than treatments typically deployed in community mental health settings (see, e.g., Weisz et al 1995a;Weisz et al 1995b). The interplay of (a) organizational characteristics, (b) implementation of empirically supported treatment, and (c) clinical outcomes is largely uncharted territory.…”
mentioning
confidence: 99%
“…While the results from rigorously controlled, academically administered field trials indicate positive effects of school-based mental health interventions, the effect size dwindles to minimum-to-negative effect size from studies done in pure mental health settings (Weisz et al, 1995) To be continued, SBS must show evidences of a significantly large positive treatment effect to justify the outlays. Without such demonstration, there is no likelihood that this, or other such SBS programs will survive the scrutiny of quality-minded program administrators.…”
Section: Caveats Pitfalls and Problemsmentioning
confidence: 89%